2017
DOI: 10.1038/s41598-017-16111-z
|View full text |Cite
|
Sign up to set email alerts
|

Null functions in three-dimensional imaging of alpha and beta particles

Abstract: Null functions of an imaging system are functions in the object space that give exactly zero data. Hence, they represent the intrinsic limitations of the imaging system. Null functions exist in all digital imaging systems, because these systems map continuous objects to discrete data. However, the emergence of detectors that measure continuous data, e.g. particle-processing (PP) detectors, has the potential to eliminate null functions. PP detectors process signals produced by each particle and estimate particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Of most importance, LM data yielded a lower standard deviation for the attenuation coefficient in comparison to even when up to four energy bins were considered. These results are in agreement with other recently conducted studies [31,32,36,46,47], which have all shown that binning of LM attributes leads to loss of information.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of most importance, LM data yielded a lower standard deviation for the attenuation coefficient in comparison to even when up to four energy bins were considered. These results are in agreement with other recently conducted studies [31,32,36,46,47], which have all shown that binning of LM attributes leads to loss of information.…”
Section: Discussionsupporting
confidence: 93%
“…To obtain the elements of the FIM for a given value of the activity and attenuation coefficient, the quantities obtained in equations ( 54)-(57) must be averaged with respect to the observed LM data at that value of the activity and attenuation coefficient. Before averaging, note that where in the second step, we use the expressions from equation (40) and equation (47), while in the third step, the mixture-model definition (equation ( 7)) is used.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a CC operator such as L may have a null space, but for the setup of section 3 and if K 3, the null space is not demanded by dimensionality considerations. Thus, it is possible that some-conceivably all-of the estimability problems inherent in the world of conventional digital imaging may disappear (Ding et al 2017b). Notice that replacing the operator H with L does not, in general, ensure that an inverse problem that was ill-posed (Natterer 1986, Bertero andBoccacci 1998) in the CD case becomes well-posed when a CC operator is used.…”
Section: The Imaging Operator Lmentioning
confidence: 99%
“…Although this paper has been limited to imaging with gamma-ray photons, the same methodology can be applied to imaging with charged particles, such as alpha and beta particles. Some work (Ding et al 2017b) has already been done in this direction, and it was shown that estimating additional parameters (such as direction and/or particle's residual energy) besides positions, does provide enormous benefits in terms of reduced null space.…”
Section: Future Workmentioning
confidence: 99%
“…In simulations of tomographic imaging with alpha or beta particles, where we can also estimate direction of travel of each particle, we have demonstrated that the null functions nearly disappear if we have 4-6 attributes per event. 30,31 3 Computational Methods for Image Science To the unitiated, concepts from image science may seem arcane, even bewildering. How do we actually compute the performance of an ideal observer or the null functions of a particular imaging system?…”
Section: Photon Counting and Photon Processingmentioning
confidence: 99%